Getting to performance: NZTrio and relational dynamics - Bathurst, Ralph; Williams, Lloyd (Organizational Aesthetics, 2014)
In this paper we examine a small arts organization - NZTrio - and its capacity to operate successfully as a cooperative, without having a designated leader. The Trio has developed highly attuned collaborative skills which enrich notions of relational leadership. We explore the history of the Trio noting the egalitarian ethos that pervades everything they undertake and the ethic of care that underpins their work together. Conversations at administrative and artistic levels are open, with ideas being held non-judgmentally. This translates into rehearsals that rely on small, nuanced gestures that inform relational leadership through an aesthetic lens.